(untitled) (Mustansiria Dental Journal, 2018)
Forty cases of pleomorphic adenoma( PA) presented in this study were diagnosed in the department of the Oral Pathology, College of Dentistry , Baghdad University covering the period 1982-1992. The tumours were distributed according to age, gender and site of occurrence. Patients ranged in age from 11 to 80 years. The age group 41-50 years was most frequently affected by PA 12 cases (30%) followed by 3rd and 4th decades 9(22.5%) 7(17.5%), respectively .It is evident in this study that PA was more frequently seen in females 24 (60%) than males16 (40%).It was observed from results that the palate was the most common site for occurrence of PA 32(80%), followed by the parotid gland 3(7.5%). Most of the results were comparable to the data of the literatures.